THU0289 Histopathological Differences Between Cutaneous Vasculitis Associated with Severe Bacterial Infection and Other Non-Infectious Cutaneous Vasculitis: Study of 52 Patients. (9th June 2015) - Santos-Gόmez, M.; Loricera, J.; González-Vela, C.; Blanco, R.; Hernández, J.L.; González-Lόpez, M.A.; Armesto, S.; Salcedo, W.; Marcellán, M.; Lόpez-Escobar, M.; Lacalle-Calderόn, M.; Calvo-Río, V.; et al.
Abstract : Background: The term "cutaneous vasculitis" (CV) includes a wide and heterogeneous spectrum of syndromes with histopathological findings that have in common vascular inflammation and blood vessel damage. Sometimes, CV can be a clinical manifestation of a severe underlying infection and its clinical features may be indistinguishable of a non-infectious CV. However, the treatment is very different: antibiotics in the case of a CV in the setting of a severe bacterial infection and immunosuppressive agents in all other cases. Objectives: Our objective was to compare the histopathological findings of skin biopsies from patients with CV associated with severe bacterial infection and those with non-infectious CV with more or less systemic involvement. Methods: We selected 3 groups from a series of patients with CV: group a) CV associated with severe bacterial infection; group b) CV without severe bacterial infection but with systemic involvement, group c) CV without systemic involvement. Only cases with available skin biopsies in optimal conditions for analysis were included. We reviewed the samples by light microscopy using H&E and Schiff periodic acid stains. A comparative study between the group a) with the other two groups (b and c) was performed. Severe bacterial infection was considered when the patient required hospitalization and received antibiotics. Results: Group a) was integrated by 12 patients (2 women/10 men; mean age; 56±15 years). The underlying severe bacterial infections were: pneumonia (n=5), meningitis (n=3), urinary tract infection (n=1), infectious arthritis of the knee (n=1), abdominal sepsis (n=1) and mediastinitis (n=1). In the group b) 21 patients were included (10 women/11 men; mean age, 52±18 years). The underlying conditions in this group were: Henoch-Schoenlein purpura (n=9), panarteritis nodosa (n=4), microscopic polyangiitis (n=2), cryoglobulinemia (n=2), neoplasia (n=2), systemic lupus erythematosus (n=1) and Sjögren syndrome (n=1). Finally, in group c) 19 patients were included (12 women/7 men; mean age: 59±24 years). The results of histopathological comparison of group a) with the groups b) and c) are shown in the table . Conclusions: In this series we observed that patients with CV associated with severe bacterial infection have more tissue neutrophilia and tend to develop more pustular dermatosis. Rather, not lymphocytosis or tissue eosinophilia was observed. However, these results need to be tested in prospective studies with larger number of patients. Acknowledgements: This study was supported by a grant from "Fondo de Investigaciones Sanitarias" PI12/00193 (Spain). This work was also partially supported by RETICS Programs, RD08/0075 (RIER) and RD12/0009/0013 from "Instituto de Salud Carlos III" (ISCIII) (Spain). Disclosure of Interest: None declared